1977
DOI: 10.1029/jb082i002p00369
|View full text |Cite
|
Sign up to set email alerts
|

The moment of inertia and isostasy of Mars

Abstract: The systematic and large deviation of the gravitational equipotential surface (EPS) of Mars from a spheroid of revolution suggests a description of Mars in terms of a spheroid nearly in isostatic equilibrium with an extra mass in the Tharsis region. The displacement from Mars and the shape of the spheroid are calculated by using this description and a Mars gravity model. The EPS is represented as a contour map of its height above the spheroid. This representation provides the first clear demonstration that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 10 publications
4
39
0
1
Order By: Relevance
“…The range of I * in (1) is used as a constraint for trial models of the internal structure of Mars. This result is close to the value of this ratio that was predicted by Reasenberg (1977) and Kaula (1979) long before the Mars Pathfinder mission.…”
Section: Introductionsupporting
confidence: 87%
“…The range of I * in (1) is used as a constraint for trial models of the internal structure of Mars. This result is close to the value of this ratio that was predicted by Reasenberg (1977) and Kaula (1979) long before the Mars Pathfinder mission.…”
Section: Introductionsupporting
confidence: 87%
“…The Viking estimate for the precession constrains the pole moment to 0.357 + 0.016. This provocative estimate lies between the upper bound 0.365 deduced by Reasenberg [1977] and Kaula et al [1989] from the assumption that the nonhydrostatic component of the observed J2 is a prolate spheroid centered on Tharsis and the value of 0.345 derived by Bills [1989] based on an alternative partitioning of the observed oblateness into hydrostatic and nonhydrostatic components.…”
Section: Introductionmentioning
confidence: 98%
“…Revision of the latter from C/MR 2 =o.377+_o.ool to o.365 + o.ooI (Reasenberg, 1977) resulted in major transfer of mass towards the planetary centre, but the history of the lunar moment-of-inertia does not inspire confidence in the latest Martian value. Cosmochemical models for the planets are also highly uncertain, and present data on the volatiles on Mars are perhaps more easily interpreted in terms of a volatile-poor than a volatile-rich planet ( Anders and Owen,I977).…”
Section: Geophysical and Geochemical Modelsmentioning
confidence: 99%